(Bez)wstyd w mediach, czyli "wszystko ujdzie". Refleksje nie do końca subiektywne - Jastrzębski, Jerzy (Studia Theologica Varsaviensia, 2017)
The hedonistic culture rejects both shame and the feeling of guilt that is connected to it. In spite of this rebellion against shame, it is an indispensable regulator of collective life and human interactions. A constructive shame protects human autonomy. It determines impassable boundaries between human beings. It allows a person to form an identity and separateness. The attitudes towards shame tend to be ambivalent. Diagnoses and assessments of this phenomenon are ambiguous, often internally contradictory, arbitrary and at the same time cautious, both in study and in everyday life. It is an individual that feels ashamed, but we can talk about a „culture of shame” or „shamelessness”, referring both to bigger and smaller human collectives. Shame and shamelessness have an exceptional place in the media. Truth and a shameless disregard for it is the aim of media manipulation. It is therefore necessary to be guided by courageous thinking and capability of assessing the shamefulness/shamelessness of the media and to stand up against the destructive and depraving principle that „anything goes”.